A necessidade da compreensão da autoridade moral no pensamento de John Finnis - Gustavo Jaccottet Freitas (Revista de Derecho)
The article presents the impact of John Finnis of thinking about the law, which must be grounded rule of law as an element that will offer you moral authority. The research is targeted at finding the rule of law spectrum finnisiano thought from three fundamental premises: 1) the meaning of the natural law; 2) The first principle of practical reason; and 3) develop the correct location of so-called basic human goods. The methodology is based on the hermeneutics of the works of Finnis and others who are investigating and comparing their views with authors like Kelsen, Ross and Alexy. The issue of human right to authority is, in fact, his authority over natural law. For human law must take into account that legal instrument that derives from a law can be considered or hierarchically superior or to be respected at risk of containing the authority of human law, precisely because it is the natural law that is with its foundation.